Hypoxia Compromises Anti-Cancer Immune Responses - Multhoff, Gabriele; Vaupel, Peter (Advances in experimental medicine and biology, 2020)
Hypoxia, one of the hallmarks of cancer, is caused by an insufficient oxygen supply, mostly due to a chaotic, deficient tumor microcirculation. Apart from a hypoxia-mediated resistance to standard therapies, modulated gene and protein expression, genetic instability and malignant progression, hypoxia also plays a pivotal role in anti-cancer immune responses by (a) reducing survival, cytolytic and migratory activity of effector cells such as CD4+ cells, CD8+ cytotoxic T cells, natural killer-like T cells and natural killer cells, (b) reducing the production and release of effector cytokines, (c) supporting immunosuppressive cells such as regulatory T cells, myeloid-derived suppressor cells and M2 macrophages, (d) increasing the production and release of immunosuppressive cytokines, and (e) inducing the expression of immune checkpoint inhibitors. In this minireview, immunosuppressive effects of hypoxia- and HIF-1a-driven traits in cancers are described.